MANAJEMEN FISIOTERAPI PADA KASUS ISCHIALGIA DEXTRA ET CAUSA HERNIA NUCLEUS PULPOSUS DENGAN MODALITAS FISIOTERAPI: A CASE REPORT - Muhammad Taufik Ilyas; Umi Budi Rahayu; Atik Hidayati (Bajang Institute, 2023)
Ischialgia is pain that occurs in the lower back radiating from the L4-S2 nerve roots in a distal direction following the path of the sciatic nerve to the lower leg. Signs and symptoms of ischialgia include limited range of motion, decreased muscle strength, and increased radiating pain. These signs and symptoms can interfere with daily activities resulting in the patient's biopsychosocial factors. Physiotherapy management by providing physiotherapy modalities such as infrared, TENS, and exercise therapy. Objective: knowing physiotherapy management to increase joint range of motion, increase muscle strength, reduce pain in cases of ischialgia dextra using physiotherapy modalities such as Infrared, TENS, and exercise therapy. Methods: This study used the case report method which was conducted at the Physiotherapy Center And Baby Spa Atik Hidayati in a male patient aged 60 years-old with complaints of lower back pain that radiated to the right leg. after specific tests the patient was diagnosed by physiotherapy as having ischialgia et causa hernia nucleus pulposus. Patients were given interventions using physiotherapy modalities 2 times a week. Result: after the intervention was implement to patient resulted increase joint range of motion, increase muscle strength, decrease in pain, increase in functional activity. Conclusion: based on this research physiotherapy management with phyisioterapy modalities such as infrared, TENS, and exercise therapy showed a good increase but not significant between before intervention and after intervention